Avaliação dos efeitos das mudanças climáticas na hidrologia da bacia do Rio Capibaribe – PE por meio da integração de projeções do CORDEX ao sistema SUPer - Silva, Gustavo Ribeiro da (2024)
Climate change poses a significant threat to water resources, intensifying extreme climate events and altering temperature and precipitation patterns. This issue can compromise water availability, requiring sustainable approaches and effective adaptations to address emerging water challenges. This study provides an analysis of the potential impacts of these changes on the water balance of the Capibaribe River Basin, located in Pernambuco, Northeast Brazil, considering the relationships between climate patterns, evapotranspiration, and hydrological flows. Simulations were conducted through the Hydrological Response Unit System for Pernambuco (SUPer), utilizing SWAT modeling as the foundational mechanism. Hydrological scenarios were generated from CORDEX projections within the 2030-2099 timeframe, under the RCP8.5 scenario, offering a detailed insight into possible future hydrological conditions in the basin. To address this issue, the research adopted the tool of sensitivity and climate variability analyses, using statistics from climate projections to feed into SUPer. Projections were derived from annual averages across all points along the basin, grouped in decadal intervals, providing a detailed analysis of future climate patterns. By applying sets of climate projections, the study mapped increases in potential and actual evapotranspiration rates compared to the reference water balance. Among the seven contexts analyzed, scenario number 4, corresponding to the 2060-2069 decade, stands out as the most critical, presenting the highest percentage growth in actual evapotranspiration (8.40%). In all situations, even with an increase in rainfall volumes, a simultaneous rise in actual evapotranspiration was observed, highlighting the complexity of the interaction between temperature and precipitation. The results also reveal a concerning trend of up to a 4 °C increase in average temperature by the end of the century, consequently elevating atmospheric water demand and emphasizing the critical need for specific adaptive strategies in the face of climate change.